PARADIGM OF ISLAMIC EDUCATION MANAGEMENT FROM THE PERSPECTIVE OF EDUCATIONAL PHILOSOPHY: DEVELOPING A STRATEGIC PLAN FOR ISLAMIC SCHOOLS - Mu'arifah, Nurvianna; Mahsun; Fatihin, Moh. Khoirul (CV. Fahr Publishing, 2024)
Islamic education management plays a crucial role in shaping a generation that excels academically and possesses strong moral and spiritual character. This study aims to analyze the paradigm of Islamic education management from the educational philosophy perspective and develop an effective strategic plan for Islamic schools. The research employs a qualitative approach through literature studies. The findings indicate that implementing the Planning, Organizing, Actuating, and Controlling (POAC) concept, based on Islamic values, enhances the effectiveness of Islamic school management. Furthermore, integrating Islamic educational philosophy into management systems enables schools to face global challenges without losing their Islamic identity. Thus, this study contributes to developing a more strategic and sustainable Islamic education management model.